Screening the fantastic – citizenship and postcolonial theoconomies in African video-film and photography. Issue 2 (3rd April 2017) - Makhubu, Nomusa
Abstract: How can the fantastic be used as a conceptual framework to think critically about citizenship in relation to the resonances between religion and capital? Through a visual analysis of Nollywood video-film as well as the photographic and video work by Nigerian photographer, Andrew Esiebo, I argue that complex relations between politics, religion and socio-economic dynamics create fantastic publics in which citizenship is continually negotiated . Intertwining economy, politics and religion through a 'theoconomy' produces publics as spectacle where transformations (from poor to wealthy, sick to healthy) are staged as symbolic exchanges. Applied in this study as a confrontation with the power of imagination, the fantastic is among the crucial ways of comprehending contemporary complexity in which uneven international economic, political and cultural relations contribute to the surreal qualities of the everyday.